The professional personnel development provision as a component of the decent work concept - Petyuh, V.M.; Schetinina, L.V.; Zinchenko, O.M. (Економіка промисловості, 2017)
In the paper modern trends of professional development in Ukraine are investigated. The analysis of survey results have defined that there are differences in beliefs of people depending on their age, development level and social status. However, the formation of an effective and sustainable economic growth of an enterprise is impossible without human development of employees, their knowledge and skills. The existence of professional development helps to reduce employee turnover, to increase their commitment and loyalty to the company and to create a favorable social and psychological climate within the collective. Development in an enterprise gives social life a sense of order and stability to workers and additional social guarantees of their employment. This is the main aspect, which allows connect an increase of the staff’s qualification level and provision of decent working conditions. In spite of this, an employer often wants to reduce expenses on vocational education and staff training because now the economic situation in the country (Ukraine) is unstable and there is a lack of necessary funds. For this reason, new technologies and development programs of staff are rarely implemented in the labor market. In particular, the disregard for the personnel needs in training leads to decrease in productivity, work motivation, reduction commitment to a company, loss of confidence and positive social interaction with colleagues and top managers. On the other hand, professional development increases business efficiency and competitiveness. Up-to-date methods of vocational training on the labour market of European Union member countries were analyzed with the aim of improving the Ukrainian training system. The experience of foreign companies is important, because they have long realized that the human capital and economy of knowledge become a source of economic growth of the enterprise.